ASSESSING SELF-EFFICACY IN VOCATIONAL STUDENTS: DEVELOPMENT AND PSYCHOMETRIC EVALUATION OF A NEW SCALE USING EXPLORATORY FACTOR ANALYSIS - Kumalasari, Rita; Sugiharto, Dwi Yuwono Puji; Sugiyo, Sugiyo; Sutoyo, Anwar (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Self-efficacy plays a crucial role in shaping students’ motivation, learning strategies, and future career readiness, especially for vocational high school students who are preparing for both academic and practical workforce demands. This study aimed to develop and validate a self-efficacy scale tailored to the context of vocational students by measuring three key dimensions: Magnitude, Generality, and Strength. Using a quantitative approach, the study involved 256 students from vocational schools in Sukoharjo Regency. The validation process employed Exploratory Factor Analysis (EFA) to test the construct validity of the scale, revealing that all items loaded significantly on their respective factors, with some items such as M3, M6, and G3 demonstrating high modification indices. This indicates a strong contribution to the model structure and areas for potential refinement. A novelty of this research lies in its contextual adaptation of the self-efficacy construct to vocational education, which is often underrepresented in psychological measurement studies. The findings confirm that self-efficacy in vocational students is a multidimensional construct and that the developed scale is both valid and reliable. The implications suggest that educators and policymakers can use this scale to design more personalized interventions aimed at enhancing students' confidence across different levels and contexts. Future research could explore longitudinal applications of the scale or its predictive validity on academic and career outcomes.